Identity, characteristics and social, economic and political development of the Costa Rican cooperatives.: Glimpses in the social economy sector. - Sánchez Boza, Ligia Roxana (Cooperativismo & Desarrollo, 2019)
Starting from the development of cooperatives in the twentieth century, this paper refers to the most important aspects of the life of the Costa Rican cooperatives, based on the legislation enacted, and taking some data offered by authors interested in this type of social entrepreneurship development. This paper highlights the political expansion of cooperativism in Costa Rican and attracts attention in the lack of recognition of the importance of the cooperatives in certain sectors such as savings and credit, and also of lack of recognition that women cooperative members suffer within the political organization of the National Council of Cooperatives. More than a century later, the Social Progress Imperative index (SPI) provides important data on the social impact of cooperativism in some of the country cantons, which proves the great importance of cooperativism in the national economy. The influence of entities such as the International Cooperative Alliance, the Advancement of Women’s equitable rights and the acceptance of international accounting standards, have generate important projects promoting gender equity, and better controls of national cooperatives, some of them successful, others are waiting for the legislative approval, such as the creation of a social economic sector, where cooperatives might have a vital role.